TECHNOLOGICAL MOTIVATION AND PERCEPTION OF SECONDARY SCHOOL STUDENTS IN ENGLISH LANGUAGE SINCE THE OUTBREAK OF COVID-19 PANDEMIC IN OSUN STATE - ABANIKANNDA, Mutahir (Universitas Negeri Semarang, 2024)
The study investigated technological motivation and perception of secondary school students in English language since the outbreak of COVID-19 pandemic in Osun State. The study is a descriptive study; a sample of 400 students from Osogbo and Olorunda, Osun Central, Osun State formed the participants for the study. The instrument for data collections was questionnaire and reliability level was 0.78. Data collected were analyzed descriptive statistics (frequency count and simple percentages), t-test and correlation. The findings of the study revealed that secondary school students perceived the roles of technological in English language since the outbreak of COVID-19 pandemic in Osun State as it is easy to use, it save time, develop interest in learning, provides communication medium for information, promote individual learning and it promote active learning. Projector, public address, multimedia software, interactive board, computer, scanner and printer are the technology facilities available for students use since the outbreak of COVID-19 pandemic while others like internet facilities, media player, Learning Management System (LMS), zoom and google classroom are not available for use. The study of the findings revealed the challenges encountered by students while using technology facilities as a motivator since the outbreak of covid-19 pandemic as ICT software is not readily available, insufficient number of ICT, insufficient technical support from ICT, absence of constant electricity, amongst others and there is no significant difference in the frequency use of technology facilities as a motivator between public and private secondary schools in Osun State. The following recommendation were made such as: the ministry of education and local government education authority should provide computers, internet and other ICT tools in all the government own schools so as to encourage teachers use of ICTs, employers of teachers should give sufficient technical skills to their employees on ICT tools, teachers training institutions like institutes of education, colleges of education, National Teachers Institutes and so on should make ICTs course compulsory for all the teachers under training to make them familiar with the use of ICTs in teaching and learning.